Tolerance to Lecanicillium fungicola and yield of Agaricus bisporus strains used in Brazil - Zied, Diego Cunha [UNESP]; Nunes, Janaira Santana; Nicolini, Vinicius Franco; Gimenez, Arturo Pardo; Rinker, Danny Lee; Dias, Eustaquio Souza (Elsevier B.V., 2015)
Dry bubble disease is a major problem in the commercial cultivation of Agaricus bisporus. In Brazil, there are no fungicides registered by the Ministry of Agriculture for control of disease in the cultivation of A. bisporus, nevertheless growers use daily fungicide on crops. The selection of strains more adapted to rustic conditions and tolerant to Lecanicillium fungicola is another alternative to avoid yield losses. Thereunto four experiments were conducted. Two cropping trials were set up in mushroom growing rooms (with and without the presence of the pathogen), and two in vitro trials with varying dilutions and active ingredient (iprodione and difenoconazole) of products were performed in lab. Our results suggest that some commercial strains of A. bisporus are more tolerant to the pathogen than others. Up to 76.5% yield loss may be caused by the pathogen under experimental conditions. Among the 15 strains studied, only one strain, ABI 11/16 was the more productive in the presence of the pathogen, even with unmarketable diseased mushrooms. The only strain that showed "in vitro" mycelial growth similar to L fungi cola was ABI 09/10; however, its yield is not high and the experimental conditions resulted in a 64% reduction in yield due to the presence of the pathogen. Difenoconazole more strongly inhibited the mycelial growth of L. fungicola than did iprodione; however, neither fungicide was selective against L. fungicola. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: White button; Dry bubble; Yield; Fungicides action; Electron micrographs